Portofolio Optimal Berdasarkan Model Indeks Tunggal Untuk Saham Lq-45 Selama Juli 2019-Juli 2020 (Universitas Gresik, 2023)
This investment is one example of economic activity carried out by a person or organization. Stocks are an investment tool. Investors should conduct a stock valuation analysis that takes into account various macroeconomic variables that affect company profitability. Theepurposeeoffthissstudyyisstoodetermine which stockssin theeLQ-45 index are most suitable for building annoptimalpportfoliooanddtoodetermineethee expecteddreturnnanddriskkoffthe portfolio from July 2019 to July. 2020. The single indicator model used is a descriptive analysis technique. Theddataauseddinnthis research is secondary data frommBEI, YahoooFinance and Bank Indonesia. This researchhwas conducted on the LQ-45 stock index of the Indonesia Stock Exchange from July 2019 to July 2020. The population for this study used stocks listed on the LQ-45 during the study period, where the research sample was 39 LQ-45 stocks indexed on period July 2019 to July 2020. Theeresultssofftheestudyyshowwthattthereeare two stocks, BRPT 76% and REP 24%, which can help you build an ideal investment portfolio with the right proportions. The expected returnnon this securityyis 5% and the risk assessment offthe portfolio is 11.9%.